2021
DOI: 10.1126/sciadv.abh2922
|View full text |Cite
|
Sign up to set email alerts
|

A molecular sensor for cholesterol in the human serotonin 1A receptor

Abstract: The function of several G protein–coupled receptors (GPCRs) exhibits cholesterol sensitivity. Cholesterol sensitivity of GPCRs could be attributed to specific sequence and structural features, such as the cholesterol recognition/interaction amino acid consensus (CRAC) motif, that facilitate their cholesterol-receptor interaction. In this work, we explored the molecular basis of cholesterol sensitivity exhibited by the serotonin1A receptor, the most studied GPCR in the context of cholesterol sensitivity, by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…Membrane cholesterol has emerged as a key modulator of the function of membrane proteins, such as GPCRs ( 95 ). Modulation of plasma membrane cholesterol offers a useful tool to address cholesterol-dependent organization and function of membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane cholesterol has emerged as a key modulator of the function of membrane proteins, such as GPCRs ( 95 ). Modulation of plasma membrane cholesterol offers a useful tool to address cholesterol-dependent organization and function of membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Cells expressing the K101A mutant serotonin 1A receptor showed similar (~51%) reduction in membrane cholesterol content upon treatment with 10 mM MβCD. Importantly, we previously showed that membrane cholesterol depletion using 10 mM MβCD did not result in a notable effect on the plasma membrane localization of the wild-type and K101A mutant serotonin 1A receptors in HEK-5-HT 1A R cells (Kumar et al 2021).…”
Section: Resultsmentioning
confidence: 92%
“…Notably, we recently attributed cholesterol-dependence of serotonin 1A receptor signaling to a CRAC motif present in the transmembrane helix 2 of the receptor (CRAC motif I, see Fig. 1) that facilitates a preferential association with membrane cholesterol (Kumar et al 2021). We showed that a key lysine residue (K101) in this CRAC motif of the serotonin 1A receptor establishes polar interaction with the hydroxyl headgroup of cholesterol and thereby acts as a molecular sensor of membrane cholesterol (Kumar et al 2021).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…With this aim we took a closer look at two types of cholesterol binding motifs, the so-called cholesterol recognition/interaction amino acid consensus (CRAC) motif with the L/V -X(1–5)- Y/F -X(1–5)- R/K pattern, and the reverse CARC motif with the R/K- X(1–5)- Y/F -X(1–5)- L/V pattern [ 36 , 37 , 38 ]. CRAC and CARC sites have been identified in transmembrane segments of several membrane proteins, such as G-protein coupled receptors, but also in membrane-interacting segments of several bacterial toxins and viral proteins that interact with cholesterol [ 39 , 40 , 41 , 42 ]. Moreover, in the aforementioned three RTX toxins (LtxA, HlyA and RtxA), CRAC sites have been identified in their pore-forming domains and for two of them, LtxA and RtxA, the interaction with cholesterol has been experimentally demonstrated [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%